A STUDY OF SOCIOECONOMIC DISADVANTAGE AND END-OF-LIFE HOSPITAL ADMISSIONS FOR OLDER PEOPLE WITH HEART FAILURE AND LUNG CANCER IN ENGLAND. Issue 1 (1st March 2013) - Hanratty, B; Lowson, E; Grande, G; Addington-Hall, J; Seymour, J; Payne, S
Abstract : Introduction: At the end of life, a move into or out of hospital is one of the most disruptive events for older adults and their carers, with consequences for their mental, physical and emotional wellbeing. Evidence from elsewhere suggests that transitions are frequent and make little contribution to patients' wellbeing. Little is known about socioeconomic differences in end of life hospital admissions in England. Aims and Methods: To investigate patterns of end-of-life hospital admissions by socioeconomic disadvantage. Analysis of linked hospital episode statistics and mortality data for England. Results: Between 2001 and 2010, 300, 304 people aged over 75 were admitted to hospital in England at least once in their last year of life with a diagnosis of lung cancer or heart failure. Eighty five percent of people admitted with lung cancer and 72% of heart failure cases underwent a transition into hospital in the last 3 months of life. In multivariate analysis, lower socioeconomic status (given by the index of multiple deprivation) being male and younger age were associated with frequent hospital admissions amongst people with heart failure (above the 90th centile). For lung cancer cases, younger age and male sex were associated with numbers of admissions above the 90th centile. People with lung cancer in the most disadvantaged IMD quintile were less likely to be admitted frequently, adjusting for age and sex. Residence in a care home was not associated with frequent admissions to hospital. Conclusions: Hospital admissions at the end of life are frequent, and vary with social disadvantage. Equitable end-of-life care in the community should be a future priority.